Rediscovery of Vadina hodeei hodeei (Oberthür, 1881) in Colombia (Lepidoptera: Castniidae) - Robert Worthy; Jorge M. González (SHILAP, 2025)
We report on a specimen of Vadina hodeei hodeei (Oberthür, 1881) collected in 2019 and several more collected in 2024. As far as we can ascertain, the previously most recently collected dated specimen was in 1931, so the subspecies hadn’t been collected for 88 years.